Type 1 diabetes vaccine candidates promote human Foxp3+Treg induction in humanized mice - Isabelle Serr (Nature Portfolio, 2016)
Type 1 diabetes is associated with the loss of self-tolerance to the insulin-producing β-cells in the pancreas. Here the authors show that vaccination with insulin mimetopes can induce human insulin-specific regulatory T cells to mediate tolerance in a humanized mouse model.